An Axiomatic Proof of Mirrlees' Formula - Stefan Homburg (Public Finance / Finances Publiques, 1998)
Mirrlees' optimal income tax formula has never been proven rigorously, and it is hard to understand it in economic terms. We prove an analogous formula for an economy with finitely many persons. This is easy and allows a simple economic interpretation. Thereafter, Mirrlees' original formula is derived by means of a limit theorem. The analysis also clarifies the discussion between Revesz and Saez published as "Communications" below in this issue of PF/FP. It shows which formula is correct and how the methodological problems, in particular the circularity problem, can be dealt with. – – Die Optimalität des von Mirrlees vorgeschlagenen Einkommensteuertarifs ist nie streng bewiesen worden. Vorliegend wird ein optimaler Tarif für endlich viele Steuerzahler bestimmt und Mirrlees' Formel durch Grenzübergang gewonnen. Außerdem enthält der Artikel Klärungen zur Diskussion zwischen Revesz und Saez um den optimalen Steuertarif.
Keywords: H21; C61; 330; Optimal income tax; Optimaler Einkommensteuertarif